2020
DOI: 10.3390/jcm9020397
|View full text |Cite|
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement with Self-Expandable ACURATE neo as Compared to Balloon-Expandable SAPIEN 3 in Patients with Severe Aortic Stenosis: Meta-Analysis of Randomized and Propensity-Matched Studies

Abstract: Frequent occurrence of paravalvular leak (PVL) after transcatheter aortic valve replacement (TAVR) was the main concern with earlier-generation devices. Current meta-analysis compared outcomes of TAVR with next-generation devices: ACURATE neo and SAPIEN 3. In random-effects meta-analysis, the pooled incidence rates of procedural, clinical and functional outcomes according to VARC-2 definitions were assessed. One randomized controlled trial and five observational studies including 2818 patients (ACURATE neo n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On review, we found 40 previous meta‐analyses discussing the risk factors of PPM implantation, however in light of the current evidence the applicability of those studies is limited. 92 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 Most of these meta‐analyses included a smaller number of previously published studies ranging from 4 to 41 articles, missing a large amount of contemporary data. The selection criteria and measured predictors were limited with respect to conduction abnormalities evaluated, indications for TAVR, and in some incidences inclusive of SAVR patients.…”
Section: Discussionmentioning
confidence: 99%
“… References 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 …”
Section: Supporting Informationunclassified
“…Smoking is one of the risk factors for respiratory infectious disorders, including viral infections. 9 Inflammatory cells infiltrate into the mucosa and glandular tissue due to smoke exposure, which leads to the excessive production of mucus. This has additional harmful effects, such as epithelial cell hyperplasia, prevention of tissue repair, thickened small bronchioles, and emphysema.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is one of the risk factors for respiratory infectious disorders, including viral infections 9 . Inflammatory cells infiltrate into the mucosa and glandular tissue due to smoke exposure, which leads to the excessive production of mucus.…”
Section: Introductionmentioning
confidence: 99%
“…The authors sincerely apologise for the imperfections made during the collection of the data and wish to make the following corrections to this paper [1].…”
mentioning
confidence: 99%